Occupational Well-Being of School Staff in Full Day and Half Day School Teachers - Rahma, Ulifa; Anggreni, Yulia Dwi; Faizah, Faizah; Dara, Yuliezar Perwira (Universitas Muhammadiyah Metro, 2020)
This research is a phenomenology study in qualitative about the portrayal of occupational well-being of school staff at Full Day School and Half Day School in Senior High School teachers, which is based on Saaranen's theory (2012). The interviews were used as data. Purposive sampling, eight primary teachers were selected, including four teachers from Universitas Negeri Malang Laboratory Senior High School as the full-day school and four teachers from Panjura Senior High School as a half-day school. Milles and Huberman were used as the data analysis following by triangulation techniques. The results showed that full-day and half-day schools needed to maintain the positive aspects that were fulfilled and improve improvement. A full-day school, the elements that have fulfilled are the workers' health and resources, professional competence, working conditions, and working communities. Meanwhile, the factors that have fulfilled are the aspects of the working community, the workers’ health and resources, and professional competence at half day school. In contrast, the element that needs to improve in this school is working conditions. Penelitian ini merupakan penelitian kualitatif jenis fenomenologi mengenai gambaran occupational well-being of school staff pada guru Sekolah Menengah Atas Full Day School dan Half Day School, yang berdasar pada teori Saaranen (2012). Data yang digunakan oleh peneliti melalui wawancara, dengan menggunakan purposive sampling sebanyak delapan guru primer diantaranya empat guru di SMA Laboratorium Universitas Negeri Malang sebagai sekolah full day dan empat guru di SMA Panjura sebagai sekolah half day. Analisis data yang digunakan yaitu analisis data Milles dan Huberman serta menggunakan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa sekolah fullday dan halfday perlu mempertahankan aspek positif yang terpenuhi dan meningkatkan hal yang masih perlu diperbaiki. Pada sekolah full day, aspek yang telah terpenuhi yaitu aspek workers health and resources, professional competence, working conditions dan working community. Pada sekolah half day, yang telah terpenuhi yaitu aspek working community, workers health and resources, dan professional competence, sedangkan untuk aspek yang perlu ditingkatkan pada sekolah ini yaitu aspek working conditions.